1997
DOI: 10.1016/s1078-5884(97)80077-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulable abnormalities and postoperative failure of arterial reconstruction

Abstract: Hypercoagulable abnormalities are common prior to arterial revascularisation and are independently associated with subsequent failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…53 Clinical studies on patients undergoing peripheral bypass surgery have demonstrated the presence of a definite subset of patients with abnormal coagulation profiles. 54 after adjusting for age and sex, von Willebrand Factor (vWF), fibrin, d-dimer and urinary fibrinopeptide a are elevated in patients with critical limb ischemia, and the risk for claudication is significantly raised with unit changes in each factor. 55,56 enhanced levels of fibrinogen, alpha-1-antitrypsin, thrombin/antithrombin iii complex, alpha-2 plasmin inhibitor/plasmin complex, and thrombomodulin were documented in claudicants.…”
Section: Risk Factorsmentioning
confidence: 99%
“…53 Clinical studies on patients undergoing peripheral bypass surgery have demonstrated the presence of a definite subset of patients with abnormal coagulation profiles. 54 after adjusting for age and sex, von Willebrand Factor (vWF), fibrin, d-dimer and urinary fibrinopeptide a are elevated in patients with critical limb ischemia, and the risk for claudication is significantly raised with unit changes in each factor. 55,56 enhanced levels of fibrinogen, alpha-1-antitrypsin, thrombin/antithrombin iii complex, alpha-2 plasmin inhibitor/plasmin complex, and thrombomodulin were documented in claudicants.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Thrombophilia defects are associated with failed revascularization in patients with peripheral vascular disease; the data suggest that the failure rate may be over three times higher than in patients without such defects1–9. Studies also suggest that hyperhomocysteinaemia is associated with vein graft stenosis10–12.…”
Section: Introductionmentioning
confidence: 99%
“…17 But in contrast to a solid association between FVL and venous thrombosis, the data relating FVL and arterial events remain controversial. Nevertheless, some clinical studies suggest an increased risk of thrombosis after arterial revascularization, [18][19][20][21][22][23][24][25] implicating vessel wall injury during the revascularization procedure as the triggering event. Not unexpectedly, the relationship between FVL and failure of arterial reconstructive procedures appears especially high in homozygotes.…”
Section: Discussionmentioning
confidence: 99%